Shakespeare Studies in Iran: The British Knight for Persia - Partovi, Parviz (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Shakespeare’s travels into Persia started in the middle of the nineteenth century when modern socio-political forces and the need for a powerful army were fomenting important changes in the traditional structure of government, production, and culture alike. Shakespeare appeared in Persia at a time when the country was experiencing a fundamental transition from older traditions into a western-like government, infrastructure, education, and ideas. Shakespeare was important to this process in two ways. He was enlisted to enrich the cultural property of the country and therefore became ensconced in the educational system. Perhaps more importantly, his plays were used to critique the ruling political system and the prevailing habits of the people. Hamlet has always been a favorite play for the translators and the intellectuals because it starts with regicide and ends with murdering a monarch and replacing him with a just king. Othello, another favorite, was frequently retranslated partly because there were similar themes in Persian culture with which readers could easily connect. Thus, Shakespeare became a Persian Knight and moved from one historical era to another to function as a mirror to reflect the aspirations of the elite, if not those of the common folk. This paper traces Shakespeare’s steps in Persia chronologically, expounding the socio-political context in which Shakespeare and his plays operated not only within the context of academia, but also without in society amongst the people and the elites as political allegories to sidestep censorship and to attack the despotic monarchs and ruling power.